The Predictive Value of Hemocytometry Based on Peripheral Platelet-Related Parameters in Identifying the Causes of Febrile Seizures - Tang L; Chen JR (Dove Medical Press, 2021)
Ling Tang,1 Jie-Ru Chen2 1Department of Clinical Laboratory, The Affiliated Wuxi No.2 People's Hospital of Nanjing Medical University, Wuxi, 214001, People's Republic of China; 2Department of Paediatrics, The Affiliated Wuxi No.2 People's Hospital of Nanjing Medical University, Wuxi, 214001, People's Republic of ChinaCorrespondence: Jie-Ru ChenDepartment of Paediatrics, The Affiliated Wuxi No.2 People's Hospital of Nanjing Medical University, Wuxi, 214001, People's Republic of ChinaTel +86 13057386807Email chenjieru_dr@outlook.comObjective: To evaluate the outcome of platelet-related parameters in children with febrile seizures (FSs) and seek low-cost markers for the clinical prediction of FSs.Methods: A total of 79 patients with FSs (the FS group) who were hospitalized in our hospital were selected. Eighty-two patients with fever and without seizures (the FC group) and 81 healthy patients without fever (the HC group) were selected. The results of whole blood cell analysis were retrospectively analyzed.Results: The results of whole blood cell analysis showed that platelet (PLT) count, mean platelet volume (MPV), hemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and hematocrit (HCT) levels in the FS group were significantly lower than in the FC and HC groups (P < 0.05). The platelet-to-lymphocyte ratio (PLR) in the FS and FC groups was significantly higher than in the HC group (P < 0.05), but there was no statistical difference between the FS and FC groups (P > 0.05). The PLT count in the CFS group was significantly lower than in the SFS group (P < 0.05). The PDW of the CFS group was higher compared with the SFS group (P < 0.05). The PLT count and PLR of the relapsed group were lower than those of the non-relapsed group (P < 0.05). The conducted linear regression analysis showed that MCH, PLT, and MPV were closely related to the occurrence of FSs. The binary logistic model showed that MPV was the most important protective factor related to FSs.Conclusion: PLT and MPV are closely related to the occurrence of FSs. PLT and PDW may be able to serve as simple yet effective laboratory indicators for distinguishing different types of FSs. Low PLR levels could be used to predict the risk of FS recurrence.Keywords: febrile seizures, hemocytes, platelet count, mean platelet volume, platelet distribution width